Enhancing structural complexity: An experiment conducted in the Black Forest National Park, Germany. Issue 1 (9th January 2023) - Asbeck, Thomas; Benneter, Adam; Huber, Alexander; Margaritis, Damaris; Buse, Jörn; Popa, Flavius; Pyttel, Patrick; Förschler, Marc; Gärtner, Stefanie; Bauhus, Jürgen
Abstract: We report on a structural complexity enhancement (SCE) experiment that was designed to test ecological restoration measures in the Black Forest National Park, Germany. The main goal was to understand as to whether the creation of standing and downed deadwood within previously managed, single‐layered Norway spruce ( Picea abies L.) forests accelerates the development of forest structure, richness, and diversity of a range of taxonomic groups. Here we introduce the experimental design and describe the development of stand structure including abundance and richness of tree‐related microhabitats (TreMs) within 5 years after initiation of the experiment in October 2016. To enhance structural complexity in treatment plots, 10 trees per plot were toppled using a skidder winch, and another 10 trees were ring barked at a height of around 60 cm above ground level with a chainsaw. To monitor stand structure, we collected data on common forest attributes such as diameter at breast height (DBH), tree height, and TreMs of all trees in the six experimental and six control plots measuring 0.25 ha in size before the treatments were carried out in 2016 and again in 2020/21. We analyzed the abundance and richness of TreMs using generalized linear mixed models with DBH and treatment vs. control as predictors. The SCE treatment resulted in a significant increase in deadwood volumes (4.2 vs. 439.5 m 3 ) as well as in TreM abundance and richness (increase of 0.74 TreMs per tree). This indicates that the SCE treatment was effective to increase biodiversity‐relevant structures such as deadwood and TreMs, in previously managed Norway spruce‐dominated stands. The ongoing monitoring of a range of taxonomic groups (birds, bats, small mammals, coleoptera, fungi, mosses, and vascular plants) in this experiment will demonstrate to what extent the enhancement in structural complexity will lead to an enrichment in species richness and diversity. Abstract : Here we report about the forest structural changes brought about by a strcutural complexity enhancement approach in secondary spruce stands in the Black Forest National Park. Five years after the initial treatment (toppling and ring‐barking of some trees), the dead wood volume and tree‐related microhabitats had significantly increased in the treated plots. Subsequent studies will show how this treatment has influenced species richness and diversity of a range of taxonomic groups.